Redescription of Dracunculus globocephalus Mackin, 1927 (Nematoda: Dracunculidae), a parasite of the snapping turtle, Chelydra serpentina - Moravec, Frantisek; Little, M D (Folia parasitologica, 2004)
Dracunculus globocephalus Mackin, 1927 (Nematoda: Dracunculoidea) is redescribed from specimens collected from the mesentery of the snapping turtle, Chelydra serpentina (L.), in Louisiana, USA. The use of scanning electron microscopy, applied for the first time in this species, made it possible to study details in the structure of the cephalic end and the arrangement of male caudal papillae that are difficult to observe under the light microscope. This species markedly differs from all other species of Dracunculus in having the spicules greatly unequal in size and shape, in the absence of a gubernaculum, and in the disposition of male caudal papillae. The validity of D. globocephalus is confirmed, but the above mentioned morphological differences are not sufficient for listing it in a separate genus. This is the first record of D. globocephalus in Louisiana.
Keywords: Animals; želvy; Nematoda; mikroskopie elektronová rastrovací; Female; Turtles; mužské pohlaví; zvířata; hlístice; Louisiana; Male; Microscopy, Electron, Scanning; ženské pohlaví